2007
DOI: 10.1111/j.1742-7843.2007.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate Inhibits the Nuclear Translocation of Nuclear Factor‐κB in Interleukin‐1β‐Stimulated Chondrocytes

Abstract: Chondroitin sulfate is referred as a symptomatic slow-acting drug for osteoarthritis because it improves articular function, and reduces joint swelling and effusion. In addition, chondroitin sulfate prevents joint space narrowing of the knee. We hypothesized that the anti-inflammatory effect of chondroitin sulfate is associated to a decrease in the activation of mitogen-activated protein kinases (MAPK) and of the transcription factors nuclear factor-κ B (NF-κ B) and activator protein-1 (AP-1). Cultured rabbit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 46 publications
4
66
0
8
Order By: Relevance
“…As a result, NF-B binds to target genes, increasing the expression of many OA-related proteins, such as pro-inflammatory cytokines (IL-1␤, IL-6, and TNF-␣) and matrix metalloproteases (MMPs) (33). In chondrocyte cultures, it has been shown that bovine CS diminishes IL-1␤-induced NF-B nuclear translocation (43), although the mechanism for this reduction remains unclear. Our data suggest that the anti-inflammatory activity of CS might be related to its effect on the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, NF-B binds to target genes, increasing the expression of many OA-related proteins, such as pro-inflammatory cytokines (IL-1␤, IL-6, and TNF-␣) and matrix metalloproteases (MMPs) (33). In chondrocyte cultures, it has been shown that bovine CS diminishes IL-1␤-induced NF-B nuclear translocation (43), although the mechanism for this reduction remains unclear. Our data suggest that the anti-inflammatory activity of CS might be related to its effect on the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Preincubation with soluble heparin and chondroitin sulphate has previously been shown to dampen the inflammatory response in cells stimulated with IL-1β, correlated with reduced NF-κB signalling, but the mechanisms of action by the polysaccharides are not clear (Hochart et al, 2006;Jomphe et. al., 2008;Legendre et al, 2008).…”
Section: ø Arlov Et Al Biomimetic Sulphated Alginate Hydrogelsmentioning
confidence: 99%
“…По-видимому, некоторые различия в механиз-мах действия ХС и ГА могут объяснить более выраженную эффективность их комбинации по сравнению с монопре-паратами [9][10][11]. Синергичный эффект ХС и ГА подтверж-ден в различных in vivo и in vitro исследованиях.…”
unclassified